2020
DOI: 10.1021/acs.jpcc.0c02456
|View full text |Cite
|
Sign up to set email alerts
|

Roughness Factor-Dependent Transport Characteristic of Shale Gas through Amorphous Kerogen Nanopores

Abstract: In the past decades, shale gas has been recognized as the promising unconventional resource for global energy storage, and a clear understanding of the gas-transport characteristic within nonporous shale organic matter (i.e., kerogen) is fundamental for the effective development of shale reservoirs. In this regard, previous studies were generally conducted based on the ideally smooth nanochannels (e.g., graphite slit or tube) without considering the atomistic-scale roughness of the walls. Herein, using molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 66 publications
3
43
0
Order By: Relevance
“…Previous MD-based research includes nanoscopic simulations of fluid flow, droplet wetting and droplet interactions with smooth and rough solid surfaces. The effect of roughness on the behavior of water nanodroplets (Yaghoubi and Foroutan 2018), wetting transition (Khan and Singh 2014;Koishi et al 2009) and gas flow characteristics (He et al 2019;Yu et al 2020) have been reported. Fang et al (2019) performed MD simulation to elaborate on the mechanisms of extracting hydrocarbon using CO 2 in a nanoscale groove constructed by silicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous MD-based research includes nanoscopic simulations of fluid flow, droplet wetting and droplet interactions with smooth and rough solid surfaces. The effect of roughness on the behavior of water nanodroplets (Yaghoubi and Foroutan 2018), wetting transition (Khan and Singh 2014;Koishi et al 2009) and gas flow characteristics (He et al 2019;Yu et al 2020) have been reported. Fang et al (2019) performed MD simulation to elaborate on the mechanisms of extracting hydrocarbon using CO 2 in a nanoscale groove constructed by silicon.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very challenging to measure the shale roughness whose length scale is less than 5 nm. However, molecular dynamics simulations have been used extensively as appropriate tools to understand the fundamentals of rock-fluid interaction in organic shale pore, for example (He et al 2019;Yu et al 2020) have studied the roughness (length scale is at 2 nanometers) effect on shale gas transport. Besides, structured surface (with close length scale in our simulation) has also widely been applied in related roughness studies via MD (Khan and Singh 2014;Koishi et al 2009;Yaghoubi and Foroutan 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such different slip behavior of methane molecules on the quartz and graphene surface is interesting; the different liquid-solid interactions are generally regarded as the main reason, which is mainly dominated by the atom's parameters σ and ε [64,65] in Table 2 for the CH 4 molecules confined in various nanopores. In addition, the breakdown of gas molecules slippage on the quartz surface is especially owing to the inherent atomic roughness of the surface by Yu et al [43,66], especially, the potential energy roughness of the quartz surface is higher than that on graphene surface up to two magnitude of orders. Thus, the gas molecules collide with the quartz surface and just go round and round and not move along the walls as what the molecules act on the graphene surface [40].…”
Section: Resultsmentioning
confidence: 99%
“…The roughness in atomic-scale roughness plays a nonnegligible role in interrupting the molecules moving along the pore wall. Furthermore, Yu et al also found that the roughness has great effect on the mass-transport of shale gas using a series of rough kerogen structures [43]. While in the MD simulation, it is not easy to control the roughness of the kerogen structure [43].…”
Section: Introductionmentioning
confidence: 99%
“…While shale nanopores are both rough and irregular, smooth graphite slit pore models have been widely used as a simplified corollary for kerogen nanopores in shale [70][71][72] . Surface roughness affects both the flow dynamics and the adsorption capacity of methane in pores [73][74][75][76] . However, given that our primary goal is to qualitatively compare retention in our model with neutron scattering observations, it warrants the use of smooth surface.…”
Section: Methodsmentioning
confidence: 99%